Clinical Presentations and Surgical Outcomes in Patients with Nontraumatic Acute Abdominal pain - Khan, Muhammad Daraz; Noor, Islam; Ahmad, Altaf; Siddiqui, Samreen Kibria; Javed, Mian Umar; Nazir, Muhammad Tariq; Waheed, Muhammad Rashid (Indus Journal of Bioscience Research, 2025)
Background: Nontraumatic acute abdominal pain is a common cause of emergency department visits, encompassing a wide range of etiologies. Accurate diagnosis and timely management are critical to improving patient outcomes. Objective: The main objective of the study is to find the clinical presentations and surgical outcomes in patients with nontraumatic acute abdominal pain. Methodology: This retrospective observational study was conducted at Khalifa Gull Nawaz Medical Teaching Institute, Bannu. from 1st September 2023 to 30th August 2024. Data were collected from 221 patients. Results: Among the 221 patients, 126 (57%) were male, with a mean age of 45 ± 15 years. The most common conditions were acute appendicitis (36%), cholecystitis (18%), and intestinal obstruction (15%). Surgical management was performed in 138 patients (62%), with appendectomy being the most common procedure (58% of surgical cases). Conservative management was successful in 90% of cases. The overall complication rate was 12%, and the mortality rate was 1.8%. Early surgical intervention was associated with shorter hospital stays (4.5 ± 1.5 days) compared to delayed surgeries (7 ± 3 days). Conclusion: It is concluded that nontraumatic acute abdominal pain requires a structured diagnostic approach and tailored management. Early surgical intervention improves outcomes, while conservative management is effective in selected cases.